PERAN PERENCANAAN STRATEGIS DALAM MENINGKATKAN KUALITAS MANAJEMEN ORGANISASI PENDIDIKAN ISLAM - Susiofianti; Gunawan, Hendri; Januar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
This study aims to analyze the role of strategic planning in improving the quality of management in Islamic education organizations. Using a library research approach, this study examines various literatures relevant to strategic planning and Islamic education management. The results show that strategic planning plays an important role in directing the vision, mission, and long-term goals of the institution, so as to improve operational efficiency, resource management, and the quality of educational services. However, the implementation of strategic planning in Islamic education institutions still faces challenges, especially in terms of limited resources and resistance to change. To overcome these obstacles, support from various parties and increased managerial capacity are needed so that strategic planning can be implemented more effectively and sustainably